Comparative study between 3 commercially available injectants for the treatment of trigger finger in the hand in Egyptian patients - Abotaleb, Ahmed Fouad (International Journal of Research in Medical Sciences, 2025)
Background: Introduction: The recent trend of using hyaluronic acid or platelet-rich plasma in injection of trigger finger rather than steroids in Egyptian population lacks a pragmatic comparative study. Pragmatic comparison of hyaluronic acid, platelet-rich plasma and steroids in the treatment of adult trigger fingers in hands. Methods: Initially 431patients were evaluated for possible inclusion in the study between August 2022 and May 2024. The condition was classified according to the modified Quinnell classification and the patients completed the visual analog scale (VAS) and Michigan Hand Outcome questionnaire (MHOQ) at the pre-injection visit, 2 weeks after injection, 6 weeks after injection and 12 weeks after injection. Results: In all groups, the 12 weeks post-injection VAS was better than the pre-injection VAS (p=0.001). The strongest statistical correlation with the final MHOQ was with the grade of the inflammation before the injection as classified by Quinnell (p<0.001). Age, gender and affection with diabetes didn’t affect the outcome. Injection with hyaluronic acid achieved better results with patients affected in their non-dominant hand with duration of symptoms less than 15 weeks and in the retiree and office-based workers subgroups. Conclusions: There is no advantage of using either hyaluronic acid or platelet-rich plasma over corticosteroids in injection of trigger finger of the hand.